Digital Technology in Strengthening Mathematical Concepts in Early Childhood: A Systematic Literature Review - Kamiliyah, Zahirotul; Roizatul Faruk; Minnatin Charizah (Noumerico: Journal of Technology in Mathematics Education, 2025)
The development of digital learning media has grown rapidly over the past decade; however, socioeconomic background has a strong influence on its use. Due to the vast diversity of users, there is no effective map. This study provides a literature review (SLR) on the use of digital technology in mathematics learning for early childhood through an analysis of 16 recent studies (studies that meet the exclusion and inclusion criteria in the PICOS framework). This paper attempts to bridge the gap between digital technology advancements and meaningful mathematics education practices. The conclusion is that game-based educational applications and interactive tools have become a primary approach proven effective in improving the understanding of basic mathematical concepts. However, behind this great potential, real challenges are found in their implementation - from the limitations of long-term studies to disparities in access across socioeconomic backgrounds. This study also highlights the need for synergy between technological innovation and appropriate pedagogical approaches. For educators, these findings provide practical guidance on selecting and implementing learning technologies, while for researchers, several critical areas are identified that require further exploration.